165k views
3 votes
X + 3x² – 28x

Can you guys help me solve this in ax^2+bx+c
Thank you thank you

1 Answer

12 votes

Answer:

3x²+(-27x) +0

Explanation:

The given expression is :

x + 3x² – 28x

We need to solve this in the form of ax²+bx+c.

we can write the given expression as :

3x²-28x+x = 3x²-27x

= 3x²+(-27x) +0

If we compare the given expression with the general expression, we find that,

a = 3, b = -27 and c = 0

Hence, the required equation is 3x²+(-27x) +0.

User Usrgnxc
by
5.5k points